The Influence of Dose Herbicide Fermented Coconut Water Raw Material Against Weeds in Immature Oil Palm Plantations - Juanda Iskandar; Risvan Anwar; Sunarti Sunarti (University of Prof. Dr. Hazairin, SH, 2023)
This study aims to determine the dosage of herbicides made from fermented coconut water against weeds in immature oil palm plantations. The research was conducted in March 2022, in Sukarami Village, Kedurang Ilir District, South Bengkulu Regency, Bengkulu Province. The experiment used a randomized block design with one factor, namely herbicide dose (D), consisting of 9 treatments: D1 = 10 L/ha, D2 = 15 L/ha, D3 = 20 L/ha , D4 = 25 L/ha, D5 = 30 L/ha, D6 = 35 L/ha, D7 = 40 L/ha, D8 = 45 L/ha, D9 = 50 L/ha. The results of the study concluded that smallholder oil palm plantations were dominated by Axonopus compresus (47.78%) and Ageratum conyzoides (30.98%). The weed that is resistant to this herbicide is Erigeron bonariensis L. The dose treatment has a significant effect on weeds in immature smallholder oil palm plantations. Treatment at a dose of 25 L/ha is effective in controlling weeds in immature oil palm plantations.